Food Quality and Nutritional Status of Pregnant and Lactating Women in The Non-Lotted Area on the Outskirts of Ouagadougou, Burkina Faso - Zoubga W. Adama (Shahid Sadoughi University of Medical Sciences and Health Services, 2021)
Background: To contribute to the fight against malnutrition among women of reproductive age, this study aimed to evaluate the quality of food and the nutritional status of pregnant and lactating women. Methods: This cross-sectional study was conducted from June 2018 to September 2018 to explore the frequency and distribution of the dietary, socioeconomic, and health characteristics of pregnant and lactating women as well as their nutritional status. The target population consisted of 124 pregnant women and 118 nursing women age between 15 to 49 years. Results: The prevalence of acute malnutrition was 30.9% among women in general, 1.6% with severe malnutrition according to the mid-upper arm circumference (MUAC). In terms of the body mass index (BMI), the prevalence of malnutrition among lactating women was 13.5%; 10.5% with moderate malnutrition and 3.5% with severe malnutrition. The women aged between 15 to 49 years had poor dietary diversity. The mean dietary diversity score (DDS) was estimated at 4.14±0.86. This score was 4.19±0.87 in pregnant women and 4.09 ± 0.85 in lactating women. However, no statistically significant difference was observed between them (P = 0.20 and OR = 0.82) [0.4; 1.4]. A substantial proportion (19.8%) of women had a low DDS (< 5), with a rate of 16.9% among pregnant women and 22.9% among lactating women. Conclusion: This study revealed the presence of food and nutrition insecurity in semi-urban areas, particularly in "undeveloped" areas. Improving the living conditions of the populations in these localities, in parallel with nutritional education actions, could help to reduce the disease.